Конструювання смислу при реалізації настанови "навчання" у міжкультурному дискурсі - Котов, Михайло Володимирович (Луганський національний університет імені Тараса Шевченка, 2013)
У статті розглядаються особливості функціонування систем смислотворення та смисловираження при реалізації настанови «навчання» під час мовленнєвої адаптації дискурсивної особистості у міжкультурному дискурсі. Встановлено, що при реалізації настанови «навчання» у міжкультурному дискурсі комуніканти можуть перебирати на себе соціальні ролі відповідно «вчителя» і «учня», що, в свою чергу, визначає особливості смислотворення та смисловираження при спробі передати нове знання (вибудувати й виразити смисл) та засвоїти або відторгнути його.

The article discusses the specificity of functioning of meaning construction and meaning expression systems when realising «knowledge discovery» guideline during discursive personality's speech adaptation within the framework of intercultural discourse. We argue that within the process of realisation of the abovementioned guideline communicants acquire social roles of correspondingly a «teacher» and a «pupil». These roles determine the functioning of the meaning construction and meaning expression systems when trying to transmit, assimilate or reject any new knowledge. A communicant, having acquired the social role of a «teacher», uses authority or authoritativeness to transmit new knowledge. A «pupil’s» active participation in the process of communication manifests itself through accepting or rejecting a «teacher’s» status, sharing or rejecting new knowledge. The latter happens due to disagreement or failure to understand. Depending on the level of adaptation of both communicants, transmission takes place with the help of non-verbal or both verbal and non-verbal codes. Interpretation in the case takes place with regard to the actual situational context on the basis of previous communicative experience.
Meaning Construction when Realising "Knowledge Discovery" Guideline in Intercultural Discourse
Keywords: полікультурна дискурсивна особистість; міжкультурний дискурс; смислотворення; смисловираження; динамічна модель значення; polycultural discursive personality; intercultural discourse; meaning construction; meaning expression; dynamic model of meaning